Kebijakan Indonesia Dalam Mewujudkan Industri Hijau (Green Industry) Masa Pemerintahan Presiden Joko Widodo - Asep Saepudin; Sri Muryantini; Herra Dwi Maghfiroh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
This article aims to describe various policies related to the development of Green Industry in the era of President Joko Widodo. this article is the result of basic research funded by UPN